Melastoma malabathricum Fruit Extract-Mediated Synthesis of Silver Nanoparticles with Sensing Ability for High Concentrations of Mercury (II) Nitrate - SALPRIMA YUDHA S; Aswin Falahudin; Meka Saima Perdani; Irfan Gustian; Saiqa Ikram (The Journal of Pure and Applied Chemistry Research, 2017)
A strategic approach was developed to synthesize silver nanoparticles from AgNO3 using Melastoma malabathricum seed extract. The reaction of silver ions with the organic compounds in the seed extract proceeded smoothly at room temperature without any additional capping agent. The appearance of an absorption peak around 427 nm provided evidence for the presence of silver nanoparticles in the reaction mixture. A diluted solution of the silver nanoparticles was treated with various concentrations of mercury (II) nitrate solutions and the resulting reaction was monitored using UV-Vis spectrophotometry